Kv4 channels underlie the subthreshold-operating A-type K+-current in nociceptive dorsal root ganglion neurons - Na Phuket, Thanawath R.; Covarrubias, Manuel L. (Frontiers in Molecular Neuroscience, 2009)
The dorsal root ganglion (DRG) contains heterogeneous populations of sensory neurons including primary nociceptive neurons and C-fibers implicated in pain signaling.  Recent studies have demonstrated DRG hyperexcitability associated with downregulation of A-type K+ channels; however, the molecular correlate of the corresponding A-type K+ current (IA) has remained hypothetical.  Kv4 channels may underlie the IA in DRG neurons.  We combined electrophysiology, molecular biology (whole-tissue and single-cell RT-PCR) and immunohistochemistry to investigate the molecular basis of the IA in acutely dissociated DRG neurons from 7-8 day-old rats.  Whole-cell recordings demonstrate a robust tetraethylammonium-resistant (20 mM) and 4-aminopyridine-sensitive (5 mM) IA.  Matching Kv4 channel properties, activation and inactivation of this IA occur in the subthreshold range of membrane potentials and the rate of recovery from inactivation is rapid and voltage-dependent.  Among Kv4 transcripts, the DRG expresses significant levels of Kv4.1 and Kv4.3 mRNAs.  Also, single small-medium diameter DRG neurons (~30 mm) exhibit correlated frequent expression of mRNAs encoding Kv4.1 and Nav1.8, a known nociceptor marker.  In contrast, the expressions of Kv1.4 and Kv4.2 mRNAs at the whole-tissue and single-cell levels are relatively low and infrequent.  Kv4 protein expression in nociceptive DRG neurons was confirmed by immunohistochemistry, which demonstrates colocalization of Kv4.3 and Nav1.8, and negligible expression of Kv4.2.  Furthermore, specific dominant-negative suppression and overexpression strategies confirmed the contribution of Kv4 channels to IA in DRG neurons.  Contrasting the expression patterns of Kv4 channels in the central and peripheral nervous systems, we discuss possible functional roles of these channels in primary sensory neurons.